Risk assessment and prevention in clinical diagnosis and treatment in implant surgery associated with systemic diseases - TANG Yufei (口腔疾病防治, 2020)
Patients seeking implantation often have several systemic diseases, which will introduce complications to treatment. This paper reviews the risk assessments and prevention of systemic diseases in patients with oral implant therapy with the relevant literature. The patients with cardiovascular diseases are prone to stroke and cardiac arrest, and anticoagulants and antihypertensive drugs will complicate cases. The potential risks of endocrine system diseases are infections and crises caused by unstable hormone levels. The risks of respiratory diseases are dyspnea and swallowing devices. The difficulty of treating patients with neuropsychiatric diseases is attributable to poor cooperation and adverse effects of the drugs. Bone and joint system diseases may decrease the success of implantation. Hematological system, digestive system and kidney diseases may lead to hemorrhage. By inquiring about detailed medical and medication history, evaluating vital signs and detecting important objective indicators, performing targeted measures, discussing with specialists, and observing patients closely, clinicians can avoid the abovementioned risks.